Targeting RAB7 in human B lymphoma by a small molecule inhibitor arrests tumor cell growth - Fernandez, Maria; Wang, Rui; Wang, Jingwei; Wu, Shuai; Holder, Kenneth; Nazarullah, Alia; Aguiar, Ricardo C. T.; Xu-Monette, Zijun Y.; Young, Ken H.; Yan, Hui; Xu, Zhenming (Frontiers in Oncology, 2025)
RAB7, encoded by RAB7A in humans and Rab7 in mice, is a small GTPase that catalyzes endosome maturation. It mediates NF-κB activation through the assembly of intracellular membrane signalosomes in stimulated normal B cells and plays a B cell-intrinsic role in the antibody response in mice. Here we show RAB7A transcripts are expressed in primary diffuse large B-cell lymphomas (DLBCLs), and that RAB7 protein expression is heightened in activated human tonsil B cells as well as in DLBCL and Burkitt lymphoma cell lines. Treating these cell lines with CID1067700, a selective small-molecule RAB7 inhibitor, results in a dose-dependent decrease in cell growth, associated with impaired proliferation and survival. CID1067700 also suppressed tumor development from Daudi cells, a Burkitt lymphoma cell line, in Foxn1nu/nu nude mice. The inhibitory effect of CID1067700 on Daudi cell growth in vitro is further enhanced by methyl-β-cyclodextrin, which disrupts plasma membrane lipid rafts, and by FX1, a BCL6 inhibitor. These findings, together with the unfavorable prognosis of DLBCL patients showing high RAB7A expression, suggest that targeting RAB7 is a promising therapeutic approach for mature B cell-derived lymphomas.